Effects of Stocking Density on Digenean Trematode and Monogenean Infections in Nile Tilapia (Oreochromis niloticus, Linnaeus 1758) Reared in Cages in Uhanya Beach, Lake Victoria, Kenya - Bwoga, J. A.; Matolla, G. K.; Raburu, P. O. (Africa Environmental Review Journal, 2021)
Cage cultured fish are susceptible to high disease incidence because of the high fish stocking densities as compared to other culture systems. This study was conducted from December 2017 to May 2018 with an objective of highlighting stocking density as a driver of monogenean and digenean trematode parasitism in Oreochromis niloticus in cages in Uhanya Beach, Lake Victoria, Kenya. The study adopted a systematic random sampling technique to sample an aggregate 600 fish during the rainy and dry seasons. Parasites isolated from the sampled fish were the monogenean Dactylogyrus and the digeneans; Tylodelphys,Clinostomum and Neascus. Dactylogyrus sp. was predominantly abundant in the fish from all the 10 cages. Mann-Whitney U-test revealed that mean intensity of Dactylogyrus sp.infestation considerably augmented with higher stocking density of fish (p < 0.05; df =298). On the contrary, Clinostomum sp., Tylodelphys sp. and Neascus sp. exhibited significantly reduced infestation with increased stocking densities (p < 0.0001). All the individual fish showed allometric growth and the general fish condition as depicted by condition factor (Kn) was significantly better in cages with stocking densities of 2500 individuals/ Cage (df = 298; p < 0.05). The relationship between intensity of parasite infestation and fish condition factor was not also weak and significant in all the parasite species (Dactylogyrus sp.: r2 = 0.017;Clinostomum sp.: r2 = 0.001; Tylodelphys sp.: r2 = 0.008; & Neascus sp.: r2 = 0.026). The study recommends proper site selection for cages, water quality management and sourcing of fish seed from certified hatcheries to prevent the spread of parasitic diseases.